Challenges associated with retrospective analysis of left ventricular function using clinical echocardiograms from a multicenter research study. Issue 2 (24th January 2021) - Sachdeva, Ritu; Stratton, Kayla L.; Cox, David E.; Armenian, Saro H.; Bhat, Aarti; Border, William L.; Leger, Kasey J.; Leisenring, Wendy M.; Meacham, Lillian R.; Sadak, Karim T.; Narasimhan, Shanti; Chow, Eric J.; et al.
Abstract: Background: Retrospective multicenter research using echocardiograms obtained for routine clinical care can be hampered by issues of individual center quality. We sought to evaluate imaging and patient characteristics associated with poorer quality of archived echocardiograms from a cohort of childhood cancer survivors. Methods: A single blinded reviewer at a central core laboratory graded quality of clinical echocardiograms from five centers focusing on images to derive 2D and M‐mode fractional shortening (FS), biplane Simpson's ejection fraction (EF), myocardial performance index (MPI), tissue Doppler imaging (TDI)–derived velocities, and global longitudinal strain (GLS). Results: Of 535 studies analyzed in 102 subjects from 2004 to 2017, all measures of cardiac function could be assessed in only 7%. While FS by 2D or M‐mode, MPI, and septal E/E′ could be measured in >80% studies, mitral E/E′ was less consistent (69%), but better than EF (52%) and GLS (10%). 66% of studies had ≥1 issue, with technical issues (eg, lung artifact, poor endocardial definition) being the most common (33%). Lack of 2‐ and 3‐chamber views was associated with the performing center. Patient age <5 years had a higher chance of apex cutoff in 4‐chamber views compared with 16‐35 years old. Overall, for any quality issue, earlier era of echo and center were the only significant risk factors. Conclusion: Assessment of cardiac function using pooled multicenter archived echocardiograms was significantly limited. Efforts to standardize clinical echocardiographic protocols to include apical 2‐ and 3‐chamber views and TDI will improve the ability to quantitate LV function.